2014
DOI: 10.1080/09540121.2014.951311
|View full text |Cite
|
Sign up to set email alerts
|

“We have to try and have this child before it is too late”: missed opportunities in client–provider communication on reproductive intentions of people living with HIV

Abstract: Men and women living with HIV with access to ARVs are living longer, healthier lives that can and often do include bearing children. Children occupy a key space in men and women's personal and social lives and often play a fundamental role in maintaining these relationships, irrespective of illness concerns. Couples living with HIV need to balance prevention needs and ill health while trying to maintain healthy relationships. Health care providers serving the reproductive needs of HIV-affected couples need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…These findings are comparable to those of Finocchario-Kessler et al (2014) in Uganda [7]. Providers also need values clarification training to help them separate their personal beliefs and clients’ rights to have children [30]. South Africa’s clinical guidelines for delivery of safer conception services need to be reviewed and adapted for use within the National Department of Health.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These findings are comparable to those of Finocchario-Kessler et al (2014) in Uganda [7]. Providers also need values clarification training to help them separate their personal beliefs and clients’ rights to have children [30]. South Africa’s clinical guidelines for delivery of safer conception services need to be reviewed and adapted for use within the National Department of Health.…”
Section: Discussionsupporting
confidence: 61%
“…Although client interviews reflected a strong need for SC counseling, provider interviews revealed their hesitancy toward providing such services given their limited knowledge, a lack of Department of Health guidelines and training, concerns about client treatment adherence, and providers’ personal beliefs [23,29,30]. Providers expressed concerns about preconception counseling and encouraging PLHIV to have children while a few noted that some providers are uncomfortable discussing sexual matters with clients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies identified provider level barriers to SCS acceptability including providers being indifferent or opposed to people living with HIV having children [22, 39, 47, 5153] or providers expressing discomfort discussing sex, especially condomless sex in patients living with HIV, thus limiting SCS discussions [20, 50, 51]. As a result, some providers did not recommend child-bearing for people living with HIV or serodiscordant couples due to secondary transmission concerns [22, 65].…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Other studies have reported that although HIVserodiscordant couples desired children, conception was rarely planned and advice was only sought after pregnancy. 46 Discussion of safer conception strategies with providers early in HIV care with male participation may reduce potential HIV transmission risk from these missed opportunities. 17 Couples with HIV-infected men need to be counseled on safer conception strategies that support fertility goals of both partners while minimizing HIV risk to the woman.…”
Section: Discussionmentioning
confidence: 99%